PENGARUH PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 5E TERHADAP KETERAMPILAN PROSES SAINS PESERTA DIDIK - Bella - Pratiwi; Fitri - Refelita; Arif - Yasthophi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This research was used experimental method that aimed to determine the effect of the application of learning cycle 5E (engagement, exploration, explanation, elaboration, evaluation) learning model to students' science process skills (SPS) on the solubility and constant solubility product material at State Senior High School number 4 in school year 2017/2018 . The method used is quasi experimental design. Samples were taken by simple random sampling technique. The sample in this research is XI IPA 4 as the control class and XI IPA 6 as the experimental class. Data collection techniques in this study is observation. Data were analyzed using t-test assisted by software SPSS 25.00 for windows software. The results of data processing obtained the value of t count = 9.546 and t table = 1.933 with a significant level of 0.000 (sig <0.05). The average N-gain value of student’s SPS in control class is 0.138 with a low category and students in experimental class 0.541 with the medium category. Based on the results of the study it can be concluded that the application of the learning cycle 5E learning model influences student’s SPS in solubility and constant solubility product material.